A case report of heart transplant for ischaemic cardiomyopathy from lupus coronary vasculitis. Issue 4 (31st October 2019) - Nandkeolyar, Shuktika; Kim, Hyungjin B; Doctorian, Tanya; Stoletniy, Liset N; Sandhu, Vaneet K; Yu, Micah; Zuppan, Craig W; Razzouk, Anees; Hilliard, Anthony; Parwani, Purvi
Abstract: Background: Coronary vasculitis is a rare, life-threatening complication of systemic lupus erythematosus (SLE). Case summary: A 23-year-old woman with SLE presented with typical angina and worsening dyspnoea on exertion. Coronary angiography revealed severe triple vessel disease with a 'string of beads' appearance classic for coronary vasculitis. Transthoracic echocardiogram revealed ejection fraction of 25–30% with a severely hypokinetic distal septum and distal anterior wall and an akinetic apical wall. Despite vasculitis treatment with cyclophosphamide and pulse-dose steroids, her coronary vasculitis did not improve. She was refractory to anti-anginal and guideline-directed medical therapy for heart failure and successfully underwent orthotopic heart transplant (OHT). Discussion: This is the first reported case of OHT in the case of SLE coronary vasculitis. Chronic SLE coronary vasculitis is caused by lymphocyic infiltration leading to inflammation and fibrosis of the major epicardial coronary arteries but can be successfully managed with OHT when refractory to medical SLE and heart failure therapies. It can affect patients of all ages with SLE, emphasizing the importance of thorough history taking and clinical evaluation in young patients presenting with cardiac symptoms to establish an appropriate diagnosis and treatment plan.